Using moderate carbon dioxide separation to improve the performance of solar-driven biogas reforming process. (1st December 2020) - Su, Bosheng; Han, Wei; He, Hongzhou; Jin, Hongguang; Chen, Zhijie; Zheng, Jieqing; Yang, Shaohui; Zhang, Xiaodong
Highlights: A two-stage biogas reforming is designed to overcome the inherent problem in old one. Moderate removal of carbon dioxide achieves the methane dry and steam reforming. The conversion rate of carbon dioxide increases from 0.08% to 40.35%. The new process saves 47.55% deionized water with an advanced thermal performance. Abstract: Biogas chemical exergy is destructed seriously in the conventional energy systems due to the direct combustion. Thermochemical conversion method is a potential way to utilize biogas chemical energy. A solar-driven two-stage biogas reforming integrated with a moderate carbon dioxide separation system is developed to overcome the inherent problems in the conventional one-stage process, including high energy and water consumption and low carbon dioxide conversion rate. By moderate removal of carbon dioxide in the new process, methane steam reforming and methane dry reforming can proceed in two reformers respectively. A comparative study was conducted to show the improvement of the carbon dioxide conversion rate, water saving ability and thermal performance in the new process comparing with the process proposed in the recent published studies. On this basis, an optimal design of the new process was explored. It was found that a lower biogas split ratio promotes the integrated performance; however, a critical biogas split ratio should be kept to avoid the carbon deposition. Unlike conventional biogas upgrading system, pursuing a high carbon dioxide separation rate in the new process is not a wise option. An optimal syngas heating value exists when the carbon dioxide separation rate reaches a middle value. This work should provide a new method to exploit the biogas chemical energy efficiently.